2019
DOI: 10.1063/1.5100150
|View full text |Cite
|
Sign up to set email alerts
|

Isomorph invariance and thermodynamics of repulsive dense bi-Yukawa one-component plasmas

Abstract: In numerous realizations of complex plasmas, dust-dust interactions are characterized by two screening lengths and are thus better described by a combination of Yukawa potentials. The present work investigates the static correlations and the thermodynamics of repulsive dense bi-Yukawa fluids based on the fact that such strongly coupled systems exhibit isomorph invariance. The strong virialpotential energy correlations are demonstrated with the aid of molecular dynamics simulations, an accurate analytical expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…The equation of state proposed by Rosenfeld and Tarazona, within the framework of an asymptotically-high density expansion for purely repulsive potentials, fits well computer simulation results in the strongly coupled stable liquid portion of the YOCP phase diagram and leads to the reduced excess internal energy expression [ 88 , 89 ]. The -dependent parameters and are given in the respective references, while the coupling parameter at the melting point, , can be conveniently expressed via Equation ( 6 ) [ 54 ]. It should be emphasized that both equations of state are strictly valid only for the stable fluid phase of the YOCP.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation of state proposed by Rosenfeld and Tarazona, within the framework of an asymptotically-high density expansion for purely repulsive potentials, fits well computer simulation results in the strongly coupled stable liquid portion of the YOCP phase diagram and leads to the reduced excess internal energy expression [ 88 , 89 ]. The -dependent parameters and are given in the respective references, while the coupling parameter at the melting point, , can be conveniently expressed via Equation ( 6 ) [ 54 ]. It should be emphasized that both equations of state are strictly valid only for the stable fluid phase of the YOCP.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The IET equations were solved with a well-established algorithm [ 52 , 54 , 58 ] that is based on Picard iterations in Fourier space combined (when necessary) with mixing and long-range decomposition techniques to facilitate convergence. The Fourier transforms are computed on a discretized domain extending up to with a real space resolution and a reciprocal space resolution .…”
Section: Computational Approachmentioning
confidence: 99%
“…The IEMHNC approach has exhibited an excellent agreement with computer simulations in recent applications to YOCP systems [36] and dense bi-Yukawa liquids. [37] In particular, a thorough investigation of the IEMHNC accuracy for the YOCP was conducted where the IEMHNC approach was validated against LD, MD, and MC simulation results over the entire dense fluid region. [36] The comparison revealed that the IEMHNC approach possesses remarkable accuracy with predictions of structural properties inside the first coordination cell within 2.0% and of thermodynamic properties within 0.5%.…”
Section: The Iemhnc Approachmentioning
confidence: 99%
“…The objective is to evaluate the performance of the recently proposed IEMHNC approach that is constructed upon the ansatz of bridge function isomorph invariance. [ 36,37 ] The IEMHNC is a very accurate integral equation theory approach, which produces excellent agreement with computer simulations of dense YOCP and bi‐Yukawa liquids. [ 36,37 ] The absence of adjustable parameters makes it an ideal candidate for time‐consuming computations such as the parametric scans of the phase diagram necessary to obtain equations of state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation